2022
DOI: 10.1111/jfpp.16552
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of PLA‐lemon essential oil nanofibrous membranes for the preservation of Mongolian cheese

Abstract: Mongolian cheese is easily contaminated by foodborne microorganisms, causing foodborne diseases and endangering public health. This study aimed to fabricate and characterize polylactic acid nanofibrous membranes loaded with lemon essential oil (PLNM), estimating their potential to be used as a novel antibacterial material for limiting the development of pathogenic microorganisms on the cheese surface. Results showed that the fibrous diameter, water contact angle, and cumulative release of the PLNM increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The E. purpurea extract has been reported to contain several phytochemicals with antimicrobial properties with demonstrated activity against several microorganisms such as Streptococcus pyogenes, E. coli, Bacillus subtilis, Mycobacterium smegmatis, Pseudomonas aeruginosa, Enterococcus faecalis, and Staphylococcus aureus [ 25 ]. Similar results have been reported by Chen et al [ 31 ] who documented a significant enhancement in microbial stability of Mongolian cheese enclosed within polylactic acid nanofibrous membranes incorporated with lemon EO (10%) during 8 days of storage at 25 °C. The nanofibrous membranes prolonged the shelf-life of Mongolian cheese till day 8 at 25 °C compared to the control cheese which exhibited excessive microbial growth on and after day 6.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The E. purpurea extract has been reported to contain several phytochemicals with antimicrobial properties with demonstrated activity against several microorganisms such as Streptococcus pyogenes, E. coli, Bacillus subtilis, Mycobacterium smegmatis, Pseudomonas aeruginosa, Enterococcus faecalis, and Staphylococcus aureus [ 25 ]. Similar results have been reported by Chen et al [ 31 ] who documented a significant enhancement in microbial stability of Mongolian cheese enclosed within polylactic acid nanofibrous membranes incorporated with lemon EO (10%) during 8 days of storage at 25 °C. The nanofibrous membranes prolonged the shelf-life of Mongolian cheese till day 8 at 25 °C compared to the control cheese which exhibited excessive microbial growth on and after day 6.…”
Section: Resultssupporting
confidence: 90%
“…A significant positive impact of nanofibrous membranes made of polylactic acid and incorporated with lemon EO has been documented by Ref. [ 31 ] on the colour and appearance and overall sensory score of Mongolian cheese during storage. The Par-Che samples wrapped with Loc-Pro-based films were also evaluated for texture profile analysis and no impact (P > 0.05) of the films was observed on the characteristics of the cheese.…”
Section: Resultsmentioning
confidence: 96%
“…Several phytochemicals with antimicrobial properties have been reported to be present in E. purpurea extract with proven antimicrobial activity against microbes such as Mycobacterium smegmatis, Streptococcus pyogenes, E. coli, Bacillus subtilis, Staphylococcus aureus , Pseudomonas aeruginosa, and Enterococcus faecalis [12] . Several studies, such as Pluta-Kubica et al [40] , Olaimat et al [41] and Chen et al [42] , have reported a significant decrease in spoilage and pathogenic microbial counts during storage for the food samples, such as cheese, packaged within the edible films containing nanoparticles as bioactive agents.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The ground samples were mixed with distilled water (40 °C) according to the ratio of 1:10 (m/v). Then, pH was measured by a digital pH meter (LeiCi PHS‐3C, Shanghai YiDian Scientific Instrument Co., Ltd. China) (Sixu et al ., 2022). Measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%